Faithful Translation in Sapardi Djoko Damono’s Poetry Translated by Harry Aveling - Ina Mutmaina (Buletin Al-Turas, 2014)
AbstraksPenelitian ini bertujuan untuk mengetahui penerjemahan puisi yang menjelaskan kesamaan efek antara pembaca bahasa sasaran dan sumber. Penelitian ini membahas tentang penerjemahan puisi Sapardi Jokodamono yang berjudul Sihir Hujan dan Yang Fana adalah Waktu ke dalam puisi berbahasa Inggris dengan judul Black Magic Rain dan Time is Meaningless yang diterjemahkan oleh Harry Avelling. Penelitian ini menggunakan metode penelitian deskriptif kualitatif analisis serta komponensial analisis berdasarkan teori Peter Newmark. Selain menggunakan metode penerjemahan setia yang diajaukan oleh Peter Newmark, penelitian ini juga menggunakan kriteria penilaian penerjemahan yang diajukan oleh Nababan, Akurasi, Keberterimaan, dan Keterbacaan. Penelitian ini menyimpulkan bahwa 99,3 % puisi ini menggunakan metode penerjemahan setia dengan membandingkan struktur gramer, kata, dan frasa. Sedangkan 0,63% dalam puisi yang berjudul Sihir Hujan tidak terlalu menggunakan penerjemahan setia. ---AbstractThe study in this paper aims to show that a good translation of poetry provides the reader with a similar effect to that gained by reading the original text. It draws upon the importance of faithful translation in Sapardi Djoko Damono’s poetry: Sihir Hujan and Yang Fana adalah Waktu translates into Black Magic Rain and Time is Meaningless that translated by Harry Aveling. The method used in this paper is descriptive qualitative analysis in which the writer describes the method of translator to transfers the poetry from Indonesian into English and componential analysis based on Newmark theories about faithful translation and the criteria of translation poetry assessment used by Nababan that used three instrument such as: Accuracy-rating instrument, Readability-rating instrument, and Instruments for measuring the acceptability of a text that used by the writer to measure the quality of translation from data analysis. From the analysis concludes that 99,37% of lines-stanza in this poetry is faithful translation by comparing the structure grammar, word, and phrase is accurate, readability, and acceptable. Then, 0,63% of other lines in poetry of Sihir Hujan are not conveyed as faithful translation and not meet the three criteria instrument of translation assessment.